2018
DOI: 10.2319/081817-559.1
|View full text |Cite
|
Sign up to set email alerts
|

Failure patterns of different bracket systems and their influence on treatment duration: A retrospective cohort study

Abstract: Bracket failure was more often observed with ceramic brackets and was associated with increased treatment duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 30 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…Robb et al (1998) [ 15 ] reported that treatment duration changes up to 46% are related to bracket failure. Literature showed that an increase of 0.3 to 0.6 times in treatment duration could be attributed to each bracket failure [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robb et al (1998) [ 15 ] reported that treatment duration changes up to 46% are related to bracket failure. Literature showed that an increase of 0.3 to 0.6 times in treatment duration could be attributed to each bracket failure [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 20% of patients from the sample presented some bracket breakage at the moment of assessment (Table 1 ). The literature shows a great variation in the prevalence of failure—from 3.5 to 23%—due to the different variables that may be considered [ 1 , 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although bonding brackets to teeth with composite resins has been a common procedure in orthodontics for many decades, bond failure during treatment is a frequently encountered problem and has a negative impact on the orthodontic treatment, such as increased chair time for the re-bond or prolonged overall treatment duration [1]. Failure of lingual brackets may have an even higher negative impact on clinical practice compared to labial appliances, because of the reduced field of view and the prefabricated individualized materials used.…”
Section: Introductionmentioning
confidence: 99%
“…Higher values were obtained byÅrtun [25], who compared the failure rates of the ceramic brackets with mechanical or chemical retention and found 1.7% and 3.2%, respectively. Recently, Stasinopoulos et al [26], in retrospective study, reported a detachment rate of the ceramic brackets of 20%. e authors, however, included in the survey only the patient with at least one bracket failure during the orthodontic treatment.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Krishnan et al [33] noted 1.7 times higher failure rate in the anterior region. Recent survey focused on the evaluation of patterns of bracket failure relates this to the increased activation forces exerted by an archwire in the crowded dental arches or increased mastication load [26].…”
Section: Discussionmentioning
confidence: 99%